2013
DOI: 10.1063/1.4820583
|View full text |Cite
|
Sign up to set email alerts
|

Predicting magnetostructural trends in FeRh-based ternary systems

Abstract: Correlations between magnetic transition temperatures and the average weighted valence band electron concentration ((s + d) electrons/atom) have led to the development of a phenomenological model that predicts the influence of elemental substitution on the magnetostructural response of bulk B2-ordered Fe(Rh1−xMx) or (Fe1−xMx)Rh alloys (M = transition elements; x < 6 at. %). Validation of this model is provided through synthesis and characterization of FeRh with Cu and Au additions. The data and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 40 publications
5
54
0
Order By: Relevance
“…Furthermore, if the AFM to FM transition is induced by an applied magnetic field, a pronounced magnetoresistance (MR) effect is found experimentally with a measured MR ratio ∼ 50% at room temperature [2][3][4]. The temperature of the metamagnetic transition as well as the MR ratio can be tuned by addition of small amounts of impurities [2,[5][6][7][8]. These properties make FeRh-based materials very attractive for future applications in data storage devices.…”
mentioning
confidence: 90%
“…Furthermore, if the AFM to FM transition is induced by an applied magnetic field, a pronounced magnetoresistance (MR) effect is found experimentally with a measured MR ratio ∼ 50% at room temperature [2][3][4]. The temperature of the metamagnetic transition as well as the MR ratio can be tuned by addition of small amounts of impurities [2,[5][6][7][8]. These properties make FeRh-based materials very attractive for future applications in data storage devices.…”
mentioning
confidence: 90%
“…heating effect onto the small volume specimen [13], [22]. Because of the elemental substitution effect due to a Pd doping [9], the phase transition temperature of FeRhPd films was decreased to around room temperature whereas that of an equiatomic FeRh alloy is around 370 K [1]. As the M -T trace makes a temperature hysteresis loop on heating and cooling arms, two transition temperatures can be determined corresponding to the two arms.…”
Section: Experimental Techniquementioning
confidence: 99%
“…This phase transition is accompanied by a large change in longitudinal and Hall resistivity [2]- [4], lattice constant [5] and entropy [6], [7]. The transition temperature is tunable around room temperature by a control of chemical composition [8], [9], so FeRh alloys are candidate materials for several applications such as heat-assisted magnetic recording [10], [11], AFM memories [12], [13], and memristor devices [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent demonstration of room temperature antiferromagnetic memory resistor 13 and electric field control of magnetic order 14 are examples, where these functional properties has been utilized. On the other hand, correlation between 'e/a' ratio and first order transition temperature (TN) has been shown by Barua et al 15 which in turn is used for synthesizing new alloys with Cu and Au substitution. Similarly, correlation between transition temperature and its rate of change with pressure/magnetic field has been reported for a wide variety of dopant in this system.…”
Section: Ugc-dae Consortium For Scientific Research University Campumentioning
confidence: 99%
“…In fact change in valence electron per atom for Ni as well as Pd substitution and its effect on first order transition is shown to be similar. 15 Opposing influence of P and H on TN has been used to study the role of P, H and T in determining the width of transition and the extent of hysteresis 18 . This study also showed that field derivative of isothermal magnetoresistance measured for various P values for a given T have similar field dependence except for shift in critical field.…”
Section: Ugc-dae Consortium For Scientific Research University Campumentioning
confidence: 99%